2011
DOI: 10.1093/nar/gkq1327
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of condensation/decondensation status of pDNA in the nuclear sub-domains by QD-FRET

Abstract: Recent studies indicate that controlling the nuclear decondensation and intra-nuclear localization of plasmid DNA (pDNA) would result in an increased transfection efficiency. In the present study, we established a technology for imaging the nuclear condensation/decondensation status of pDNA in nuclear subdomains using fluorescence resonance energy transfer (FRET) between quantum dot (QD)-labeled pDNA as donor, and rhodamine-labeled polycations as acceptor. The FRET-occurring pDNA/polycation particle was encaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…This tendency was also observed in a previous study, in which 14DMAE and 29DMAE were employed as an artificial condenser [11]. Additionally, we showed that the cationic density in DMAE-SS-PRX has a positive influence on the efficiency of DNA release in the nucleus in living cells [10], suggesting that the conditions used in the in vitro experiment would reflect the condition of the nucleus. In this study, we used condensed pDNA particles at an N/P ratio of 5 in all of the DMAE-SS-PRXs.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This tendency was also observed in a previous study, in which 14DMAE and 29DMAE were employed as an artificial condenser [11]. Additionally, we showed that the cationic density in DMAE-SS-PRX has a positive influence on the efficiency of DNA release in the nucleus in living cells [10], suggesting that the conditions used in the in vitro experiment would reflect the condition of the nucleus. In this study, we used condensed pDNA particles at an N/P ratio of 5 in all of the DMAE-SS-PRXs.…”
Section: Discussionsupporting
confidence: 88%
“…In vitro DNA release experiments showed that pDNA was efficiently released from the condensed pDNA particles, when DMAE-SS-PRX with a high cationic density was used [11]. Moreover, we provide evidence to show that cationic density in DMAE-SS-PRX clearly has a positive influence on the efficiency of DNA release in the nucleus in living cells, resulting in high gene expression, as evidenced by imaging the nuclear condensation/decondensation status of pDNA using a new technology [10] Based on the previous results, we hypothesized that a high cationic density in DMAE-SS-PRX would aid nuclear DNA release, resulting in strong transgene expression. In this study, we first screened the optimal DMAE-SS-PRX for nuclear DNA release.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Furthermore, some efforts directed to the use of the NLS failed to enhance the transfection efficacy in JAWS II cells or primary mouse bone marrow-derived dendritic cells (BMDCs). As an alternate approach, we attempted to overcome the nuclear membrane as well as the endosomal membrane via step-wise membrane fusion [68,69]. In this strategy, we developed a tetra-lamellar MEND (T-MEND), in which the pDNA/polycation complex particle was coated with nucleus-fusogenic lipid (composed of caldiolipin and DOPE) and an endosome-fusogenic lipid (composed of phosphatidic acid and DOPE).…”
Section: Control Of the Intracellular Trafficking For Pdna Deliverymentioning
confidence: 99%